Exploring similarities : Internationalization decision-making processes of instrumental musicians and entrepreneurs - Osella, Vittoria (My University, 2025)
This thesis examines the internationalization decision-making processes of instrumental mu-sicians and explores their similarities with entrepreneurial strategies. By analyzing the career paths of three Italian musicians, a pianist and two trombonists, this study identifies how they recognize opportunities, assess risks, and develop strategies for career growth. It highlights how musicians, like entrepreneurs, engage in strategic planning, risk management, and net-working to expand internationally. However, while entrepreneurs tend to follow structured business models driven by market demand, musicians often pursue passion-driven careers that require balancing artistic expression with financial stability. The research applies entrepreneurial theories, such as effectuation, opportunity recognition, and heuristic decision-making, to the careers of instrumental musicians. The findings reveal that musicians rely on intuitive, experience-based decision-making when navigating uncer-tainty and international markets. Cultural intelligence plays a crucial role, as musicians con-tinuously adapt to diverse audiences, performance traditions, and institutional expectations. Unlike traditional entrepreneurs, they operate in a highly competitive and reputation-driven environment, where access to global opportunities depends on personal networks, audi-tions, and cultural institutions. This study has also contributed to the discussion on cognitive biases and heuristics in deci-sion-making under uncertainty. It demonstrates that musicians, like entrepreneurs, use cog-nitive shortcuts to evaluate opportunities, mitigate risks, and make career decisions. Howev-er, they must also navigate unique challenges, such as maintaining artistic integrity while meeting commercial demands. By bridging research from entrepreneurship and the creative industries, this thesis enhances the understanding of internationalization beyond traditional business contexts. It provides valuable insights for scholars, musicians, and industry professionals, offering practical impli-cations for career development, risk management, and strategic decision-making. Ultimately, the study underscores the importance of adaptability, networking, and entrepreneurial thinking in building sustainable international careers in the music industry.
Keywords: entrepreneurship; decision making; internationalisation; musicians; fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business